2022
DOI: 10.3390/nano12071038
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Supported Nickel Nanoparticles at Low Exposure to O2: Charging Effects and Selective Surface Activity

Abstract: The oxidation of Ni nanoparticles supported on highly oriented pyrolytic graphite was investigated under conditions of low exposure to oxygen by methods of scanning tunneling microscopy and spectroscopy. It was found that charge transfer effects at the Ni-C interface influenced the surface activity of the nanoparticles. The O2 dissociation and the Ni oxidation were shown to occur only at the top of the nanoparticle, while the border of the Ni-C interface was the less preferable area for these processes. The O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…A region is formed along the perimeter where the nanoparticle retains the former electronic structure of the metallic type. The experiment completely reproduces the results of our previous work, where we assumed that this locality of oxide formation is due to the excessive charge of the nanoparticle and its influence on oxygen diffusion [27]. However, several factors are most likely to work here, as in the case of gold.…”
Section: Nickelsupporting
confidence: 84%
See 2 more Smart Citations
“…A region is formed along the perimeter where the nanoparticle retains the former electronic structure of the metallic type. The experiment completely reproduces the results of our previous work, where we assumed that this locality of oxide formation is due to the excessive charge of the nanoparticle and its influence on oxygen diffusion [27]. However, several factors are most likely to work here, as in the case of gold.…”
Section: Nickelsupporting
confidence: 84%
“…This was proven in experiments with N2O, which dissociates at room temperature on platinum nanoparticles and is quickly followed by stable Pt-O formation. In the case of nickel nanoparticles, we did not manage to observe any intermediate forms of oxygen adsorption against the background of oxide formation [27].…”
Section: A Quick Glance At the Adsorption Mechanismmentioning
confidence: 78%
See 1 more Smart Citation
“…Among these different types of semiconductors, nickel oxide (NiO), this oxide exists in a deformed form because of the existence of excess oxygen atoms, and this leads to the formation of holes among the neighbouring ions of Ni 2+ ions, thus lead to the oxidation of nickel ions from (Ni 2+ to Ni 3+ ). Generally, changes in the color of this oxide result from this process 28 . In heterogeneous photocatalytic systems, nickel oxide can be employed singly or in combination with a supported co-catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…35 Recent experimental studies have demonstrated the influence of an external constant electric field (or the applied potential, which is equivalent to the electric field) to various types of reactions: the processes of hydrogen reduction of oxidized platinum, 36 hydrogen chemisorption on gold nanoparticle surfaces, 37,38 decomposition of ammonia on organoboron nanoparticles 39 and platinum nanoparticles, 40 and hydrogenation of ethylene on a nanostructured platinum coating. 41 The premise of the presented study was work, 42 which established the influence of an external electric field on the processes of reduction of an oxidized copper nanoparticles surface interacting with carbon monoxide by the methods of scanning tunneling microscopy and spectroscopy.…”
Section: Introductionmentioning
confidence: 99%